2015
DOI: 10.1667/rr13807.1
|View full text |Cite
|
Sign up to set email alerts
|

Drug Metabolism and Homologous Recombination Repair in Radiosensitization with Gemcitabine

Abstract: Gemcitabine (difluorodeoxycytidine; dFdCyd) is a potent radiosensitizer, noted for its ability to enhance cytotoxicity with radiation at noncytotoxic concentrations in vitro and subchemotherapeutic doses in patients. Radiosensitization in human tumor cells requires dFdCyd-mediated accumulation of cells in S phase with inhibition of ribonucleotide reductase, resulting in ≥80% deoxyadenosine triphosphate (dATP) depletion and errors of replication in DNA. Less is known of the role of specific DNA replication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(45 reference statements)
2
3
0
Order By: Relevance
“…In their treatment schedules, cells were treated 24 h before irradiation with gemcitabine and at time of irradiation, approximately 45% of cells were in S-phase [11]. Indeed, Im et al presented that radiosensitization with gemcitabine required a depletion in deoxynucleotide for approximately 4 h with accumulation of cells in S-phase [12]. These observations are coherent with our hypothesis that gemcitabine could synchronize cell lines into S-phase, thus leading to enhanced sensitization after irradiation and olaparib treatment.…”
Section: Discussionsupporting
confidence: 85%
“…In their treatment schedules, cells were treated 24 h before irradiation with gemcitabine and at time of irradiation, approximately 45% of cells were in S-phase [11]. Indeed, Im et al presented that radiosensitization with gemcitabine required a depletion in deoxynucleotide for approximately 4 h with accumulation of cells in S-phase [12]. These observations are coherent with our hypothesis that gemcitabine could synchronize cell lines into S-phase, thus leading to enhanced sensitization after irradiation and olaparib treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Our results and the reports from others found that BRCA2 (and likely other genes involved in HR) is required for the cytotoxicity of gemcitabine [ 24 , 25 ]. BRCA2-deficient cells are more resistant to gemcitabine treatment compared to the BRCA2-restored cells ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, a defect in homologous recombination (HR) is expected to sensitize cells to gemcitabine. However, previous reports indicated that homologous recombination (HR) is indeed required for the cytotoxicity of gemcitabine [ 24 , 25 ]. We examined sensitivity to gemcitabine in BRCA2-defective ovarian cancer cell line PE01 and its BRCA2-revertant PE01(C4-2).…”
Section: Resultsmentioning
confidence: 99%
“…Gemcitabine (difluorodeoxycytidine; dFdCyd) inhibits DNA replication and was found to radio-sensitize a wide range of cancer cell models in vitro [ 104 , 105 ]. Although the mechanism of sensitization is not yet clear, recent evidence suggests that gemcitabine lowers the threshold for radiation-induced apoptosis [ 106 ]. An open-label, single-arm phase I/II trial in newly diagnosed DMGs explored the potential and safety of gemcitabine administered concomitantly with RT.…”
Section: Dna Repair As a Therapeutic Target To Radio-sensitize Dmgmentioning
confidence: 99%